Edge irregular a;-labeling for several classes of trees - Asim M.A.; Ahmad A.; Hasni R. (Utilitas Mathematica, 2019)
Motivated by the definitions of the irregular labeling of a graph defined by Chartrand et al. [10] in 1988 and Baca et al. [8] in 2007, Ahmad et al. [5] in 2014 define the edge irregular fc-labeling of a graph. In this paper, we show that several types of trees, namely non-homogeneous caterpillar, homogeneous lobster and homogenous amalgamation star graph admits the edge irregular fc-labeiing. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.